MR Imaging-Related Heating of Deep Brain Stimulation Electrodes: In Vitro Study - Finelli, Daniel A.; Rezai, Ali R.; Ruggieri, Paul M.; Tkach, Jean A.; Nyenhuis, John A.; Hrdlicka, Greg; Sharan, Ashwini; Gonzalez-Martinez, Jorge; Stypulkowski, Paul H.; Shellock, Frank G. (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: Recent work has shown a potential for excessive heating of deep brain stimulation electrodes during MR imaging. This in vitro study investigates the relationship between electrode heating and the specific absorption rate (SAR) of several MR images.METHODS: In vitro testing was performed by using a 1.5-T MR imaging system and a head transmit-receive coil, with bilateral deep brain stimulation systems positioned in a gel saline-filled phantom, and temperature monitoring with a fluoroptic thermometry system. Standardized fast spin-echo sequences were performed over a range of high, medium, and low SAR values. Several additional, clinically important MR imaging techniques, including 3D magnetization prepared rapid acquisition gradient-echo imaging, echo-planar imaging, quantitative magnetization transfer imaging, and magnetization transfer-suppressed MR angiography, were also tested by using typical parameters.RESULTS: A significant, highly linear relationship between SAR and electrode heating was found, with the temperature elevation being approximately 0.9 times the local SAR value. Minor temperature elevations, <1°C, were found with the fast spin-echo, magnetization prepared rapid acquisition gradient-echo, and echo-planar clinical imaging sequences. The high dB/dt echo-planar imaging sequence had no significant heating independent of SAR considerations. Sequences with magnetization transfer pulses produced temperature elevations in the 1.0 to 2.0°C range, which was less than theoretically predicted for the relatively high SAR values.CONCLUSION: A potential exists for excessive MR imaging-related heating in patients with deep brain stimulation electrodes; however, the temperature increases are linearly related to SAR values. Clinical imaging sequences that are associated with tolerable temperature elevations in the ≤2.0°C range at the electrode tips can be performed safely within an SAR range <2.4 W/kg local (0.9 W/kg whole body averaged).